Grandmaternal smoking increases asthma risk in grandchildren: A nationwide Swedish cohort. Issue 2 (10th October 2017) - Lodge, C. J.; Bråbäck, L.; Lowe, A. J.; Dharmage, S. C.; Olsson, D.; Forsberg, B.
Summary: Background: There is growing interest in exposures prior to conception as possible risk factors for offspring asthma. Although partially supported by evidence from limited human studies, current evidence is inconsistent and based on recall of exposure status. Objective: We aimed to investigate grandmaternal smoking during pregnancy and the risk of asthma in grandchildren using prospectively collected population‐based data. Methods: Information on grandmaternal and maternal smoking during pregnancy and grandchild use of asthma medications was collected from national Swedish registries. Associations between grandmaternal smoking during pregnancy (10‐12 weeks) and asthma medication use in grandchildren were investigated using generalized estimating equations. Ages at which asthma medications were prescribed classified childhood asthma into never, early transient (0‐3 years), late onset (3‐6 years) and early persistent (0‐3 and 3‐6 years) phenotypes. Results: From 1982 to 1986, 44 583 grandmothers gave birth to 46 197 mothers, who gave birth to 66 271 grandchildren (born 1996‐2010). Children aged 1‐6 years had an increased asthma risk if their grandmothers had smoked during pregnancy, with a higher risk for more exposure (10+ cigs/d; adjusted OR 1.23; 1.17, 1.30). Maternal smoking did not modify this relationship. Conclusions & Clinical Relevance: Children had an increased risk of asthma in the first 6 years of life if their grandmothers smoked during early pregnancy, independent of maternal smoking. Importantly, this exhibited a dose‐response relationship and was associated with a persistent childhood asthma phenotype. These findings support possible epigenetic transmission of risk from environmental exposures in previous generations.